Web-Based Batik Sales System Uses Locking Mechanism to Prevent Race Condition - Wirayuda, Hassan; Usman, Ari (Journal of Technology and Computer, 2025)
The development of information technology is driving digital transformation in various sectors, including trade. This research aims to design and build a web-based batik sales system equipped with a locking mechanism to address race conditions, which occur when multiple users access data simultaneously, which can lead to data inconsistencies. The system was developed using PHP and MySQL, focusing on online transaction management and real-time stock updates. The results show that the system is capable of handling concurrent transactions well. The application of the locking mechanism to critical processes successfully maintains data consistency and prevents conflicts due to simultaneous access. Black-box testing proves that all system functions operate as required. This research is expected to provide practical solutions for batik MSMEs and serve as an academic reference regarding concurrent transaction management and data integrity.